Pengaruh getah pepaya (Carica papaya) terhadap sintasan tokolan udang windu (Panaeus monodon) pada kepadatan yang berbeda selama pengangkutan - Wahyu Tursina; Sofyatuddin Karina (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2013)
Abstract. The objective of present study was to evaluate the possibility of papaya’s latex (Carica papaya) as anti stress or larvaside for tiger shrimp (Panaeus monodon) post larvae Pl 14-30 during transportation. The tiger shrimp post larvae was collected from BBAP Ujung Batee, Aceh Besar on September, 2012. Reseach method used the completely random design with two factors, density of post larvae with three treatments (1000; 1500 dan 2000 ind/l) and concentration of papaya’s latex with four treatments (0; 100; 200 dan 300 ppm) and three replications for each treatments. The effect of papaya’s latex on tiger shrimp post larvae was observed by calculating the percentage of post larvae’s survival rate. The calculation was only done after twelve hours of transportation, due to the everage of survival rate percentage of post larvae on all levels of density was less than 50%. The ANOVA test showed that the density and the concentration factors gave significance effect on survival rate of tiger shrimp post larvae (P0,05). The results showed that survival rate of tiger shrimp post larvae (PL 14-30) were decreased with increasing of larvae density and concentration of papaya’s latex. However, Duncan’s test showed that the highest survival rate was obtained at 1.000 ind/l and 0 ppm of papaya’s latex. Hence, the effect of papaya’s latex concentration treatments in this study was larvaside on tiger shrimp post larvae.Key words: Closed transportation system, dissolved oxygen, enzyme papain, tiger shrimp post larvae.